The Readiness of Discharge planning in Aspects of Caregiver Involvement among Caring for the Elderly with Stroke - Lita Heni Kusumawardani; Rahmi Setiyani; Asep Iskandar; Pramono Pramono; Dwi Ichsan Supardi (Media Keperawatan Indonesia, 2023)
The elderly with stroke depend on the people around them, so caregivers must be around the patient. Its readiness to care for the elderly with a stroke can cause the treatment to be not optimal so that it pays attention to the needs of the elderly. This study aimed to determine the readiness of discharge planning in the aspect of the involvement of elderly caregivers with stroke. The study was carried out within eight months. This type of research is descriptive exploratory with a cross-sectional study design and uses a purposive sampling method for 102 respondents with criteria that match the research sample. The inclusion criteria were that the respondent is the main caregiver for the elderly with stroke. Data analysis in this study used univariate analysis and data collection tools like questionnaires. The questionnaire was declared valid and reliable (r-value > 0.361; Cronbach's alpha = 0.811). The respondents (caregivers) in this study obtained results with an age range of 17 to 74 years, and the median value of the respondent's age data is 43 years. The elderly age ranges from 60 to 88 years, and the median value of the respondent's age data is 67 years. The client's length of stay is in the range of 3-14 days, with a median value of 5 days of treatment. The description of the implementation of the readiness discharge planning in the aspect of caregiver involvement in caring for the elderly with stroke is in a good category, as many as 60 people (58.82%). Nurses are expected to maintain and improve discharge planning services for caregivers, especially stroke patients, to improve nursing care and quality of life for stroke patients.